Headmaster's Strategy on Teacher Professional Competency to Improve the Quality of Education in SMK Negeri 2 Semarang - Suliarsi, Suliarsi; Sugiyo, Sugiyo; Utanto, Yuli (Educational Management, 2021)
The purpose of this study was to find out how the principal's leadership strategy on the professional competence of teachers to improve the quality of education. This study also seeks to identify various obstacles faced in the professional competence of teachers as well as the professional competence of teachers that are suggested in the future in improving the quality of education. The object of this research is SMK Negeri 2 Semarang. While the subjects in this study are teachers, principals, and vice principals. The research method uses qualitative methods. The results of this research indicate that to improve the quality of education at SMKN 2 Semarang is divided into two strategic activities; The first is a formal strategy, namely teachers are assigned by institutions to attend education/training, either by the school itself or by educational/training institutions. The second is a non-formal strategy, namely the teacher for his desire and effort to train and develop himself related to his work or position such as discipline, discussion, and motivation. There are several obstacles faced in developing the professional competence of teachers to improve the quality of education at SMKN 2 Semarang, among others: the lack or limitation of IT mastery in schools and limited time, the lack of teacher creativity in the learning process in the classroom, and the lack of a collection of books or school facilities, and lack of scientific work made by the teacher.